The significance of primary health care design evolution to health trend in Malaysia - Mohd Nawawi, Norwina (2004)
Primary Health Care (PHC) in any country provides the accessibility and backbone to the nation’s health as first point of contact for people and the healthcare system. In Malaysia, besides the mushrooming of general practitioners (GPs) in the private sector found only in urban areas, the public sector healthcare system covers the whole country in many location and forms. The study is thus to rediscover the significance of the design evolution in this sector of healthcare to the health trend of the country that makes Malaysia as one of the worlds’ successful developing country meeting the WHO slogan Health for All by 2000.